Hubungan Pengetahuan dan Sikap Tentang Anemia, Kebiasaan Makan dengan Kejadian Anemia pada Mahasiswi Fakultas Teknik Universitas Negeri Surabaya - Ari Wahyuni; Choirul Anna Nur Afifah (Lembaga Pengembangan Kinerja Dosen, 2025)
Iron deficiency anemia is a common condition that occurs in female students, influenced by many factors such as knowledge, attitudes and eating habits. This study aims to determine the relationship between knowledge and attitudes about anemia, eating habits with the incidence of anemia in female students at the Faculty of Engineering, Unesa. This study used a cross-sectional design. Sample from this study were 105 female students from 10 study programs. The data measured were knowledge and attitudes of anemia, eating habits containing intake of iron, vitamin C, calcium, and hemoglobin (Hb) levels. Bivariate analysis using the Spearman's Rank Test. The data showed that the majority of respondents had moderate knowledge (55.2%), positive level for attitude (49.5%), iron intake was severe deficit level (70.5%), excessive of vitamin C intake (40.9%) and calcium intake at a severe deficit level (99%). The results of the bivariate test showed a relationship between several variables with the incidence of anemia , such us knowledge about anemia (p = 0.000 <0.05), attitude of anemia (p = 0.007 <0.05), and eating habits of vitamin C (p = 0.007 <0.05). While the habit of iron and calcium intake showed no relationship with the incidence of anemia (p = 0.083> 0.05) and (p = 0.107> 0.05). It concluded that knowledge and attitude about anemia also intake of vitamin C have relation with the incidence of anemia in female students at faculty of engineerig, Unesa while the intake of iron and calcium does not.